Pluripotentne matične celice v embrionalnem razvoju in pri odraslem - Jež, Mojca (Farmacevtski vestnik, 2012)
According to their capabilities for differentiation stem cells can be totipotent, pluripotent, multipotent and unipotent. After fertilization, zygote is the ultimate totipotent cell. Cells arising durring embryonic development have a lesser potency. Different pluripotent cell types are known: embryonic stem cells, embryonic germ cells, induced pluripotent stem cells, epiblast stem cells, and still controversial pluripotent stem cells isolated from the adult tissues. It is currently recognized that every tissue contains a small population of stem cells that are capable of self-renewal and differentiation. Embryonic stem cells have the broadest potential for differentiation because they are capable of turning into every cell type in our bodies. This is the reason why they are the most interesting for use in medicine. Lately, a lot of new studies have shown that somatic stem cells have broader potency than it has been expected until now and at the same time do not have any of embryonic stem cell drawbacks.
Keywords: embrionalne celice; embrionalni razvoj; embryonic development; embryonic stem cells; matične celice; pluripotency; pluripotentnost; somatic stem cells; somatske celice